2019
DOI: 10.18535/jmscr/v7i10.82
|View full text |Cite
|
Sign up to set email alerts
|

Marital dissatisfaction and perceived social support as predictors of depression among married individuals

Abstract: This study investigated marital dissatisfaction and perceived social support as predictors of depression among married individuals. The participants for this study comprised of 276 members of Catholic Men Organization (CMO) and Catholic Women Organization (CWO) of Awka Diocese, selected through the use of simple random sampling technique. Their age ranged from 24 to 55 years, with a mean of age of 46.12 and a standard deviation of 18.34. Instruments administered on them included Index of Marital Satisfaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Nonetheless, other research has shown a connection between Appraisal support and marital happiness. According to research by Okoli, Ezeme, and Ofojebe (2019), couples that lack evaluation support are more likely to experience discomfort and have higher levels of marital unhappiness. Affirmation and positive feedback, among other characteristics, were found to increase marital satisfaction in a separate study by Njeri (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, other research has shown a connection between Appraisal support and marital happiness. According to research by Okoli, Ezeme, and Ofojebe (2019), couples that lack evaluation support are more likely to experience discomfort and have higher levels of marital unhappiness. Affirmation and positive feedback, among other characteristics, were found to increase marital satisfaction in a separate study by Njeri (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Both men and women are equally vulnerable to developing major depressive disorder if their marriage is strained. Okoli, Ezeme, and Ofojebe (2019) conducted research in Nigeria to find out if marital discontent and perceived social support are related to an increased risk of depression for married people. This research project involved a cross-sectional survey of the Catholic men's organization (CMO) and the Catholic women's organization (CWO) in the Awka Diocese.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the pressure placed on clergy spouses to be strong, capable leaders in their homes, churches, and communities, some couples feel they have no choice but to hide the difficulties they are experiencing. Okoli, Ezeme, and Ofojebe (2019) claim that unhappiness in a marriage might have significant effects on both partners' physical and mental health. For instance, it raises the possibility of damaging conflict patterns.…”
Section: Introductionmentioning
confidence: 99%